Restoring physiological levels of ascorbate slows tumor growth and moderates HIF‐1 pathway activity in Gulo−/− mice. (30th October 2014) - Campbell, Elizabeth J.; Vissers, Margreet C. M.; Bozonet, Stephanie; Dyer, Arron; Robinson, Bridget A; Dachs, Gabi U.
Abstract Hypoxia‐inducible factor‐1 (HIF‐1) governs cellular adaption to the hypoxic microenvironment and is associated with a proliferative, metastatic, and treatment‐resistant tumor phenotype. HIF‐1 levels and transcriptional activity are regulated by proline and asparagine hydroxylases, which require ascorbate as cofactor. Ascorbate supplementation reduced HIF‐1 activation in vitro, but only limited data are available in relevant animal models. There is no information of the effect of physiological levels of ascorbate on HIF activity and tumor growth, which was measured in this study. C57BL/6 Gulo−/− mice (a model of the human ascorbate dependency condition) were supplemented with 3300 mg/L, 330 mg/L, or 33 mg/L of ascorbate in their drinking water before and during subcutaneous tumor growth of B16‐F10 melanoma or Lewis lung carcinoma (LL/2). Ascorbate levels in tumors increased significantly with elevated ascorbate intake and restoration of wild‐type ascorbate levels led to a reduction in growth of B16‐F10 (log phase P < 0.001) and LL/2 tumors (lag growth P < 0.001, log phase P < 0.05). Levels of HIF‐1α protein in tumors decreased as dietary ascorbate supplementation increased for both tumor models (P < 0.001). Similarly, tumor ascorbate was inversely correlated with levels of the HIF‐1 target proteins CA‐IX, GLUT‐1, and VEGF in both B16‐F10 and LL/2 tumors (P < 0.05). The extent of necrosis was similar between ascorbate groups but varied between models (30% for B16‐F10 and 21% for LL/2), indicating that ascorbate did not affect tumor hypoxia. Our data support the hypothesis that restoration of optimal intracellular ascorbate levels reduces tumor growth via moderation of HIF‐1 pathway activity.